MEDIA GAMBAR DALAM PEMBELAJARAN IPS DI MADRASAH IBTIDAIYAH - -, Mochamad Makhsun (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2021)
Image media is a medium that can be seen by the sense of vision that is explained through images in the learning process that aims to make it easier for children to understand lessons more quickly. The application of image media in ips learning in MI is one example is in class V semester I, namely on the basic competencies of respecting the diversity of ethnic groups and cultures in Indonesia. The goal is through the observation of images of students can identify the diversity of ethnic groups and cultures in Indonesia. Identify ethnic and cultural diversity in Indonesia, such as traditional houses, traditional clothing, dances and traditional weapons. In the above learning activities the teacher needs the appropriate image media.